Legal writings on foreign investment in Vietnam (H. Socialist republic of Vietnam, 1992)
Content of this book are provisions of investment law; provisions of taxation; provisions of bank and foreign exchange; provisions of technology transfer, industrial property and quality of goods; provisions of customs,...
Keywords: Luật học